Desain Pembelajaran Penjumlahan dan Pengurangan Pecahan Dengan Menggunakan Timbangan Siswa Kelas IV - Rahmawati (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
This study aims to generate trajectories of students in the learning addition dan subtraction fractions by using scales that evolved from the informal to the formal form. The method used in this study is a research design that consists of three stages, ie preliminary, design experiments and retrospective analysis. In this study, a series of learning is designed and developed based on the notion of the learning process and approach PMRI. This research was conducted in MI Al-Hilaliyah Palembang involving fourth graders totaling 30 siswa.penelitian produces Learning Trajectory (LT), which includes three activities, namely the activity 1. Considering the object and determine the equivalent fractions of fractions of known 2. define relationship occurred between two fractions to determine whether two fractions are equivalent fractions or not. Activity 3. solving the problems associated with fractional operation daily life - today. The results of the learning experiments showed that a series of activities that have been done to help improve students' understanding of the addition dan subtraction of learning fractions.